Analysis of the Effect Between Operating Cash Flow, Profitability Ratio and Earnings Per Share on Share Price in Banking Sector in 2015-2019 - Siti Nurul Khomariah (Perkumpulan Praktisi Akuntansi Indonesia, 2021)
Changes in share price are influenced by several aspects. In this study using operating cash flow variables, the level of profitability ratios and earnings per share. From the company's operating cash flow, investors can measure the company's performance in allocating its funds. And investors need to measure the level of company profitability and earnings per share in order to see and assess the profit that will be received by investors. This purpose of this research to analyze the level of influence of operating cash flow and profitability and earnings per share on stock prices. This research is quantitative and the data source used is the financial statements duplicated annually by the IDX for 5 years from the 2015-2019 period. The research subjects are banking companies listed on the IDX. The results showed that cash flow had no effect on stock prices in the banking sector, while the level of profitability ratios and earnings per share had a significant effect on stock prices on the IDX. Simultaneously, the operating cash flow variable, the level of profitability ratio and earnings per share have an effect on banking stock prices.